The Effect Of Work-Family Balance On Job Satisfaction Of Female Education Personnel At Yogyakarta State University: A Quantitative Study - Anik Pralestiningsih; Siti Rohmah Nurhayati (Universitas PGRI Yogyakarta, 2026)
This study aims to examine: (1) the work-family balance among female educational staff at Yogyakarta State University, (2) job satisfaction among female educational staff at Yogyakarta State University, and (3) the influence of work-family balance as a predictor of job satisfaction among female educational staff at Yogyakarta State University. This research employed a quantitative approach. The population consisted of all married female educational staff across 17 divisions at Yogyakarta State University, totaling 222 individuals. The sample, comprising 140 respondents, was selected using a proportional random sampling method. Data were collected using a work-family balance scale and a job satisfaction scale. Construct validity and reliability were tested using Cronbach’s Alpha. Data were analyzed using simple linear regression analysis. The results showed that: (1) the majority of respondents had a high level of work-family balance (84 individuals or 60.0%), (2) the majority had a high level of job satisfaction (81 individuals or 57.9%), and (3) simple linear regression analysis revealed a significant effect of work-family balance on job satisfaction (β = 1.215; p < 0.001), with a contribution of 34.7%, while the remaining 65.3% was influenced by other factors not included in the study variables. These findings highlight the importance of implementing work flexibility policies to enhance job satisfaction among female educational staff. Keywords: work-family balance, job satisfaction, universitas negeri yogyakarta